North meets South : theoretical aspects on the Northern and Southern rock art traditions in Scandinavia - Skoglund, Peter, 1967-; Ling, Johan, 1968-; Bertilsson, Ulf (Swedish rock art series, 2017)
This latest volume in the 'Swedish Rock Art' series bridges the gap between analysis and interpretation of rock art imagery, location and chronology in the northern and southern regions of Scandinavia. Long viewed as belonging to distinctive regional traditions, there are many underlying similarities, themes and formats in common, overlain by regional complexities and variations. The authors explore new approaches and methods of analysis. There has been a tendency in rock art research to focus merely on either the Northern Tradition or the Southern Tradition of Scandinavian rock art and there is certainly a need to broaden this discussion. Thus, the aim of this collection of new research papers is to stimulate different perspectives and themes that place emphasis on the intersection between these traditions. North meets South puts the focus on Scandinavian rock art regardless of regions and traditions. Even though there are obvious differences in space and time regarding these two traditions, there are also features and formats in common across both time and space, and a significant theme running through the contributions presented here is to highlight the interaction between these rock art traditions. A major conclusion to be drawn from this exercise is the great complexity and variation of rock art and the need for perspectives comparing various regions across Scandinavia. This volume is the outcome of an international symposium organised by the Swedish Rock Art Research Archives (SHFA).